Kajian Awal Varietas Kopi Arabika Berdasarkan Ketinggian Tempat di Dataran Tinggi Gayo - Hifnalisa Hifnalisa; Abubakar Karim (Fakultas Pertanian, Universitas Syiah Kuala, 2008)
Early Study on Arabica Coffee Varieties Base on Altitude Position on Gayo Highland AreaABSTRACT. Farmer cultivated mixed-varieties of arabica coffee in an area. As result no specific tasted for specific variety found. This result aims to observe the best coffee to be recommended for various altitude cultivation. There are nine altitude variations, 100 m interval from 700 to 1600 m above sea level (asl). For each internal altitude, coated-red coffee been harvested at farmers coffee farms at almost the same management and growth. The variables of arabica coffee bean quality physically observed were coated-red raw bean, coffee beans, coffee quality , beans passed on various filters, bean shape and tasted. The result showed that arabica coffee bean quality physically is getting better till 1400 m asl and then tends to decrease the quality till 1600 m asl as shown in export quality percentages, no passed at 7.50 mm filter, the percentage of normal beans, and tasted scores. However for coated-red raw asl. In contrast, floating coated-bean, floating bean and normal beans is decrease. Catimor Jaluk Variety of coffee arabica is suitable for all altitudes observed, followed by arabusta, Lini-S, Bergendal, and USDA. To avoid the dissimilarity of specific taste to highland arabica coffee, the varieties could be extended at different areas even though the same altitude.